Variation Evaluation of Path Characteristic and Site Amplification Factor of Earthquake Ground Motion at Four Sites in Central Japan - Nagao, T. (Engineering, Technology & Applied Science Research, 2021)
The considered parameters in seismic design vary, with the Earthquake Ground Motion (EGM) having the largest variation. Since source characteristic, path characteristic, and Site Amplification Factor (SAF) influence the EGM, it is crucial to appropriately consider their variations. Source characteristic variations are mainly considered in a seismic hazard analysis, which is commonly used to evaluate variations in EGM. However, it is also important to evaluate variations in path characteristic and SAF with only a few studies having individually and quantitatively examined the variations of these two characteristics. In this study, based on strong-motion observation records obtained from four sites in central Japan, the three characteristics were extracted from seismograms using the concept of spectral inversion. After removing the source characteristic, the path characteristic and SAF were separated, and the variations in these two characteristics were quantified. To separate and obtain each characteristic from the observed record, one constraint condition must be imposed, whereas the variations in the constraint condition must be ignored. In that case, the variations in the constraint condition are included in the variations of the separated characteristics. In this study, this problem was solved by evaluating the variation in the constraint condition, which is the SAF at a hard rock site, by the use of the vertical array observation record at the site.